Effect of Arterial Hypertension on Postoperative Mortality and Morbidity after Off-pump CABG Surgery (Cardiovascular Journal, 2017)
Background: Arterial hypertension is one of the leading modifiable risk factor in coronary artery disease patients who underwent coronary artery bypass grafting (CABG) with the major impact on clinical outcome in these patients. This study was done to evaluate the effect of arterial hypertension on postoperative mortality and morbidity after off-pump CABG.Methods: 200 patients with mean age of 52 ± 6 years, (182 male/18 female) undergoing off pump CABG were divided equally into two groups, 100 patients with hypertension (Group A) and 100 patients without hypertension (Group B). Postoperative mortality and morbidities (Wound infection, AMI, TIA, Stroke) up to 6 months were recorded in the 2 groups.Results: In comparison with the normotensive patients, hypertensive patients had a higher mortality rate (Group A 10% and Group B 2%, p value-